1999
DOI: 10.1007/s002849900423
|View full text |Cite
|
Sign up to set email alerts
|

Specific Detection of Xylella fastidiosa Pierce's Disease Strains

Abstract: Pierce's disease (PD, Xylella fastidiosa) of grapevine is the primary pathogen limiting vinifera grape production in Florida and other regions of the southeastern United States. Quick and accurate detection of PD strains is essential for PD studies and control. A unique random amplified polymorphic DNA (PD1-1-2) was isolated from a PD strain from Florida. Fragment PD1-1-2 was cloned, sequenced, and found to be 1005 bp in length. PCR primers were designed to utilize these sequence data for PD strain detection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
0
16
0
4
Order By: Relevance
“…Insects, including the glassy-winged sharpshooter (5), are the vectors for transmitting these diseases. Xf can be differentiated into subspecies or pathovars depending on such criteria as plant host specificity and pathogenicity (2,(6)(7)(8)(9)(10)(11). We will refer throughout to the citrus, almond, and oleander strains as: Xf pv citrus (XFA), Xf pv almond (XFX), and Xf pv oleander (XFY).…”
mentioning
confidence: 99%
“…Insects, including the glassy-winged sharpshooter (5), are the vectors for transmitting these diseases. Xf can be differentiated into subspecies or pathovars depending on such criteria as plant host specificity and pathogenicity (2,(6)(7)(8)(9)(10)(11). We will refer throughout to the citrus, almond, and oleander strains as: Xf pv citrus (XFA), Xf pv almond (XFX), and Xf pv oleander (XFY).…”
mentioning
confidence: 99%
“…The greater than 70% similarity indicated that X. fastidiosa was a single species (11); however, no meaningful phylogenetic relationships could be defined. Randomly amplified polymorphic DNA analysis (RAPD) led to a more comprehensive phylogenetic classification of a larger variety of X. fastidiosa plant-host pathovars distributed across its range, such as grapevine (western United States), mulberry and oak (eastern United States), and coffee (South America) (1,4,10,14,20,26). Similarity indices of the RAPDs indicated that bacteria isolated from the same plant-host species were more similar than bacteria from different hosts (20).…”
mentioning
confidence: 99%
“…Due to the presence of economically important crops in this list, Xf has been the subject of increasing attention in recent years (Hartung et al 1994;Chen et al 1995;Pooler and Hartung 1995;Banks et al 1999), leading to the complete genomic sequencing of a strain (9a5c) associated with CVC in Brazil, which turned out to be the first plant bacterium to have its complete genome elucidated. This work also involved an extensive in silico evaluation of the bacterium's presumed proteome, allowing the formulation of a virtual metabolome that provided a comprehensive view of the major biochemical processes that occur in this microorganism (Simpson et al 2000).…”
mentioning
confidence: 99%